Evolução da microbiota contaminante em linha de processamento de queijos Minas frescal e ricota - Santos, Vidiany Aparecida Queiroz [UNESP]; Hoffmann, Fernando Leite [UNESP] (My University, 2010)
Fresh cheeses such as Minas frescal and ricotta are excellent means for undesirable microorganisms to thrive, damaging quality and wholesomeness of these products. In this context, this study aimed at evaluating the contaminating microorganisms in the processing line of fresh cheese, namely Minas frescal and ricotta, of a dairy plant nestled in the city of São José do Rio Preto-SP. The analyses were carried out with the following steps: water, pasteurized milk, curd, mass, whey, palmar surface and coagulation tank, and cheeses with zero and five days of shelf life. Such steps were monitored by determining the MLN of total coliforms and thermotolerants; counting of coagulase-positive Staphylococcus and mesophilic aerobic bacteria; search of Escherichia coli, Salmonella spp. and Listeria monocytogenes. Twelve samples were evaluated in each step. Among the water samples, three are provided with higher values than the ones recommended in terms of mesophilic aerobic bacteria. Three milk samples did not comply with thermotolerant coliforms. The mass samples, curd and whey showed a decrease in the counting for all microorganisms. Both palm surface and coagulation tank showed low counting for all bioindicators. All milk samples showed compliance regarding phosphatase/peroxidase.

Queijos frescos como o Minas frescal e a ricota são excelentes meios para a proliferação de microbiota indesejável, prejudicando a qualidade e a integridade destes produtos. Nesse contexto, este estudo objetivou avaliar a evolução da microbiota contaminante em linha de processamento de queijos Minas frescal e ricota, de uma indústria de laticínios localizada no município de São José do Rio Preto-SP. As análises foram realizadas nas seguintes etapas: água, leite pasteurizado, coalho, massa, soro, superfície palmar dos manipuladores e tanque de coagulação, e queijos nos tempos zero e cinco dias de vida de prateleira. Tais etapas foram monitoradas por meio da determinação do NMP de coliformes totais e termotolerantes; contagem de Staphylococcus coagulase positiva e bactérias aeróbias mesófilas; pesquisa de Escherichia coli, Salmonella spp. e Listeria monocytogenes. Foram avaliadas doze amostras em cada uma das etapas. Das amostras de água, observou-se que três das amostras apresentaram valores acima do estabelecido para bactérias aeróbias mesófilas. Três amostras de leite apresentaram-se em desacordo para coliformes termotolerantes. As amostras de massa, coalho e soro apresentaram reduções nas contagens para todos os microrganismos. A superfície palmar e tanque de coagulação apresentaram baixas contagens para todos os bioindicadores. Os queijos apresentaram inconformidade para Staphylococcus coagulase positiva. Todas as amostras de leite apresentaram conformidade quanto à fosfatase/peroxidase.
Evolution of microbial contaminants in the processing line of Minas frescal and ricotta cheeses
Keywords: bioindicadores; queijo Minas frescal; ricota; fosfatase/peroxidase; bioindicators; Minas frescal; ricotta cheese; phosphatase/peroxidase